Dejeto líquido de suínos e manejos de solo na sucessão aveia/milho/trigo duplo propósito/soja - Fabbris, Cristiano (2013)
Swine production in southern Brazil is concentrated on small farms, seeking the recovery of waste as a source of nutrients crops of economic interest. The interaction between applications of pig slurry and soil management is common on small farms, however scarce information was found about the main responses of agricultural crops under this condition. Thus, the present work aimed to evaluate the use of pig slurry, associated with soil management in succession oat / maize and double purpose wheat / soybean. The experimental design was a factorial in a randomized complete block design, with four replications. The treatments consisted of doses of pig slurry (without manure, 20, 40, 80 m3 ha-1), and mineral fertilizer in three different soil management: no tillage, chiseling and chiseling + disking. The application of pig slurry was held before oat/maize and wheat crops sowing, and the soil management employed only before the establishment of winter crops. The application of pig slurry in succession oat / maize showed increases in dry matter yield, and in the accumulation of nitrogen, phosphorus and potassium, and in the grain yield. As for soil management, no-tillage favored the production of oat dry matter yield and soybean grain yield. However, the dual-purpose wheat proved to be low responsive to soil management employed. As for maize, the interaction between higher doses of pig slurry and with tillage managements promotes increases in grain yield. The application of pig slurry before the dual purpose wheat sowing promoted increases in dry matter production and grain yield. The residual effect of five applications of pig slurry does not alter the soybean grain yield.